Hepatitis C in men who have sex with men in London – a community survey. Issue 9 (18th June 2013) - Price, H; Gilson, R; Mercey, D; Copas, A; Parry, J; Nardone, A; Johnson, A; Hart, G
Abstract : Objectives: For the last 10 years there has been an epidemic of hepatitis C virus (HCV) infection in men who have sex with men (MSM) in Europe, North America and Australia. The majority of those infected are also HIV‐positive and it is unclear to what extent HIV‐negative MSM are also at increased risk of infection with HCV. This study provides the first examination of the association between HIV and hepatitis C serostatus in a sample of MSM recruited in community settings. Methods: A total of 1121 participants completed a short questionnaire in 2008/2009 giving demographic and behavioural data, and donated a sample of oral fluid that was subsequently tested for antibodies to selected pathogens (HIV, syphilis and HCV). Results: The seroprevalence of hepatitis C antibody was 2.1% [95% confidence interval (CI) 1.4–3.2%]. It was more common in those with HIV infection [7.7% (95% CI 4.2–12.9%) vs. 1.2% (95% CI 0.6–2.1%) in those without HIV infection; P  < 0.001], those with a history of syphilis [12.2% (95% CI 4.6–24.8%) vs. 1.7% (95% CI 1.0–2.6%) in those without such a history; P  < 0.001] and those who reported casual unprotected anal intercourse in the previous year [4.1% (95% CI 2.0–7.4%) vs. 1.2% (95% CI 0.5–2.2%) in those who did not report such intercourse; P  = 0.01]. There was no relationship between hepatitis C antibody (anti‐HCV) status and other demographic variables (age, ethnicity, employment status or education). Conclusions: The seroprevalence of anti‐HCV in HIV‐negative MSM (1.2%) was higher, but not significantly higher, than that in the general population (0.67%). The prevalence was significantly higher in those infected with HIV or with previous syphilis infection and in those reporting unprotected anal intercourse. Our findings support current British Association for Sexual Health and HIV guidelines recommending the provision of selective HCV testing in MSM according to individual risk profile.